Comparative methodological studies of L-asparaginase encapsulation into erythrocytes - D. V. Borsakova; M. E. Plakhotnik; L. D. Koleva; E. A. Bovt; Yu. G. Alexandrovich; F. I. Ataullakhanov; E. I. Sinauridze (Онкогематология, 2018)
Background. L-asparaginase is an enzyme, widely used in the therapy of acute lymphoblastic leukemia in children and adults, but its use is limited due to a wide range of side effects and anaphylactic reactions. L-asparaginase loaded into erythrocytes can solve these problems. This enzyme is protected from the immune system and plasma proteases due to erythrocyte membrane, but continues to work inside the cell because its membrane is permeable to L-asparagine. Thus, the half-life of the drug increases and anaphylactic reactions reduce. The encapsulation of L-asparaginase into erythrocytes can be performed by various osmotic methods. Each of them is characterized by the amount of encapsulated enzyme, the cell yield, as well as by the quality indices of the survived erythrocytes. An important parameter of each method is the possibility to provide sterility of this dosage form for the clinical use.The aim of the study was the comparing of three osmotic methods of L-asparaginase encapsulation into erythrocytes (hypo-osmotic lysis, dialysis and flow dialysis) to select the most promising method for clinical use.Materials and methods. A suspension of erythrocytes of healthy donors (hematocrit 60–70%) was mixed with L-asparaginase from E. сoli. The procedures of hypotonic reversible lysis, dialysis in dialysis bags, or flow dialysis using pediatric dialyzers were performed. The physiological osmolality was restored in suspensions after the procedure by the addition of a hypertonic solution, and they were incubated for 30 min at 37 °C. Then the cells were washed in isotonic phosphate-buffered saline with pH 7.4. Activity of L-asparaginase, volume, hematocrit, hematological indices and osmotic cell fragility of erythrocytes were measured in the suspensions of erythrocytes before and after the enzyme encapsulation procedure.Results. An optimal osmolality of the hypotonic buffer for each method was selected and was equal to 90–110 mOsm/kg. The yields of encapsulation were 4.2 ± 2.0, 6.0 ± 2.3 and 16.2 ± 2.2 % for hypotonic lysis, dialysis and flow dialysis, respectively. The hematological indices of the obtained erythrocyte-carriers differed from the corresponding parameters of the initial erythrocytes, but did not differ significantly for different methods.Conclusion. Comparative investigation of mentioned above parameters allowed choosing the method of flow dialysis as the most promising for clinical use.